Mitochondrial Oxidative Phosphorylation Nuclear-Encoded Genes, Enzyme Regulation, and Pathophysiology - Kadenbach, Bernhard; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This book will describe the nuclear encoded genes and their expressed proteins of mitochondrial oxidative phosphorylation. Most of these genes occur in eukaryotic cells, but not in bacteria or archaea. The main function of mitochondria, the synthesis of ATP, is performed at subunits of proton pumps (complexes I, III, IV and V), which are encoded on mitochondrial DNA. The nuclear encoded subunits have mostly a regulatory function. However, the specific physiological functions of the nuclear encoded subunits of complexes I, III, IV, and V are mostly unknown. New data indicates that they are essential for life of higher organisms, which is characterized by an adult life without cell division (postmeiotic stage) in most tissues, after the juvenile growth. For complex IV (cytochrome c oxidase) some of these subunits occur in tissue-specific (subunits IV, VIa, VIb, VIIa, VIII), developmental-specific (subunits IV, VIa, and VIIa) as well as species-specific isoforms. Defective genes of some subunits were shown to induce mitochondrial diseases. Mitochondrial genes and human diseases will also be covered.
Preface -- Introduction -- Mitochondrial Dynamics: The Intersection of Form and Function -- Biogenesis of Mitochondrial Proteins -- Assembly Factors of Human Mitochondrial Respiratory Chain Complexes: Physiology and Pathophysiology -- Supramolecular Organization of the Mitochondrial Respiratory Chain: A New Challenge for the Mechanism and Control of Oxidative Phosphorylation -- Molecular Mechanisms of Superoxide Production by the Mitochondrial Respiratory Chain -- Studies on the Function and Regulation of Mitochondrial Uncoupling Proteins -- Evolution of the Couple Cytochrome C and Cytochrome C Oxidase in Primates -- Reaction Mechanism of Mammalian Mitochondrial Cytochrome C Oxidase -- Phosphorylation of Mammalian Cytochrome C and Cytochrome C Oxidase in the Regulation of Cell Destiny: Respiration, Apoptosis, and Human Disease -- Individual Biochemical Behavior Versus Biological Robustness: Spotlight on the Regulation of Cytochrome C Oxidase -- Bigenomic Regulation of Cytochrome C Oxidase in Neurons and the Tight Coupling Between Neuronal Activity and Energy Metabolism -- Cytochrome C Oxidase and its Role in Neurodegeneration and Neuroprotection -- The Many Clinical Faces of Cytochrome C Oxidase Deficiency -- Index.
Keywords: Medicine; Human genetics; Gene expression; Cytology; Biomedicine; Human Genetics; Gene Expression; Cell Biology